Volatiles from Sophora japonica flowers attract Harmonia axyridis adults (Coleoptera: Coccinellidae) - Chun-li XIU; Bin XU; Hong-sheng PAN; Wei ZHANG; Yi-zhong YANG; Yan-hui LU (Journal of Integrative Agriculture, 2019)
The multicolored Asian lady beetle, Harmonia axyridis (Coleoptera: Coccinellidae), is a common generalist predator in China and is occasionally found gathering on the Chinese pagoda tree, Sophora japonica, in summer. In a field investigation, we found that H. axyridis adults preferred S. japonica during its flowering period even though their optimal prey (aphid) is absent at this time. In addition, male and female adults were attracted to S. japonica flowers to a similar extent in a Y-tube olfactometer assay. Using coupled gas chromatography-electroantennogram detection (GC-EAD), we identified a flower odor component (nonanal) that elicited a significant electrophysiological response in H. axyridis. Electroantennogram (EAG) dose-dependent responses revealed that the amplitude of the adult beetle's EAG response increased with increasing concentration of nonanal, peaking at 10 mg mL−1. In Y-tube olfactometer behavioral tests, H. axyridis adults preferred a 10 mg mL−1 nonanal source over a 100 mg mL−1 diluent. Under field conditions, the adults were significantly attracted to both concentrations (10 and 100 mg mL−1), and high concentrations generally had greater attraction. All these results suggest that nonanal, a volatile compound of S. japonica flowers, greatly attracts H. axyridis adults. This study provides a basis for the development of synthetic attractants of H. axyridis, with the potential to promote biocontrol services of this generalist predator in the native area (e.g., China) and to suppress its population by mass trapping in its invasive areas.